Stabilitas Lereng Perkuatan Dinding Penahan Tanah Menggunakan Software GEO5 dan Perhitungan Empiris pada Proyek Jalan Lintas Selatan Lot 1A STA 4+600 - Ramadhan, Arya Galih; Sefrina, Ani; Farichah, Himatul (Universitas Batanghari Jambi, 2025)
Jalan Lintas Selatan LOT 1A is located in Brumbun to Sine Beach, Tulungagung Regency which stretches for 9.560 kilometers. The existing condition of the southern coast of Tulungagung regency is surrounded by steep and steep rocky hills that require excavation and embankment work that will produce a slope. In the construction project of Jalan Lintas Selatan (JLS) LOT 1A STA 4+600 there is a slope located on the shoulder of the road. Slope planning with retaining walls is needed to prevent landslides. Retaining walls are built to maintain slope stability and protect the main road infrastructure. In this study, slope stability calculations with retaining wall reinforcement were carried out using GEO5 software and empirical calculations. In the GEO5 software, the slope is modeled and analyzed according to the existing slope conditions before and after being reinforced with retaining walls. The results obtained were that the slope without reinforcement showed a factor of safety value of 1.45. This value does not meet the minimum standard set in SNI 8460:2017. To improve the stability of the slope, an analysis was carried out by adding retaining wall reinforcement, which resulted in a safety factor value of 2.20, exceeding the minimum standard set, namely SF ≥ 1.5 In addition to the slope stability analysis, an evaluation of the retaining wall was also carried out to ensure its safety against the danger of overturning, sliding, and collapse of the soil bearing capacity. The calculation of the safety factor of the retaining wall was carried out using the empirical method and numerical analysis with Geo5 software. The results of the software analysis showed safety factor values of 6.48 for overturning, 5.43 for sliding, and 3.01 for bearing capacity collapse. Meanwhile, the empirical calculation results showed values of 3.44 for overturning, 5.37 for sliding, and 3.20 for bearing capacity collapse.